Akuntabilitas dan Transparansi Pengelolaan Keuangan Masjid Di Kota Mataram - Sumarni; Rusli Amrul; Rusdi (Akuntabel: Jurnal Ilmiah Akuntansi, 2023)
This research aims to find out how accountability and transparency are implemented in the financial management of mosques in the city of Mataram. This research uses a descriptive qualitative approach. The data sources used are primary data and secondary data. Data collection techniques in this research used interviews, documentation and observation. This research uses data validity testing with an interal validation (creadibility) test carried out by triangulation. The results of this research show that the six mosques have presented and disclosed all mosque financial management activities and have fulfilled the transparency, ease of mosque financial information and are easy to understand by the congregation at the six mosques in the city of Mataram. So that mosques in the city of Mataram have implemented accountability quite well and implemented transparency better.